معذورکا مفہوم اور اقسام :اسلام اوربین الاقوامی نقطہ نظر میں(ایک تجزیاتی مطالعہ): The Concept and Types of Disability: An Analytical Study in Islamic and International Perspectives Doi:https://doi.org/10.5281/zenodo.16784366 (Khairulummah, 2024)
The article titled "The Concept and Types of Disability: An Analytical Study in Islamic and International Perspectives" provides a comprehensive exploration of disability from both Islamic and global viewpoints. It examines the definition of disability, its different classifications, and the ways in which societies perceive and respond to individuals with disabilities. Drawing on Islamic texts, the study highlights how disability is understood within the framework of Islamic theology, ethics, and law, offering a unique perspective on inclusion and the rights of persons with disabilities. The article also compares these views with international standards, particularly the United Nations Convention on the Rights of Persons with Disabilities (CRPD), to analyze how global policies address issues related to disability, inclusion, and empowerment. By examining both religious and secular approaches, the paper seeks to identify common ground and potential areas of conflict between Islamic and international perspectives. This comparative analysis not only enhances the understanding of disability in diverse contexts but also advocates for a more inclusive approach, emphasizing the need for global cooperation in creating a more equitable environment for individuals with disabilities. The study contributes to ongoing discourse on disability, providing valuable insights for policymakers, scholars, and religious leaders alike.
Keywords: Disability, Islamic theology, international perspectives, inclusion, rights of persons with disabilities